Development of a conceptual framework for a group-based format of the Lifestyle-integrated Functional Exercise (gLiFE) programme and its initial feasibility testing - Kramer-Gmeiner, Franziska; Labudek, Sarah; Jansen, Carl-Philipp; Nerz, Corinna; Fleig, Lena; Clemson, Lindy; Becker, Clemens; Schwenk, Michael (Pilot and feasibility studies, 2020)
The Lifestyle-integrated Functional Exercise (LiFE) programme is a fall prevention programme originally taught in a resource-intensive one-to-one format with limited feasibility for large-scale implementation. The aim of this paper is to present the conceptual framework and initial feasibility evaluation of a group-based LiFE (gLiFE) format developed for large-scale implementation.